Using Kgen to Generate Cross‐Verified Apparent Equilibrium Constants (K∗’s) for Palaeoseawater Carbonate Chemistry - Ross Whiteford; Oscar Branson; Dennis Mayk (Geochemistry, Geophysics, Geosystems)
Abstract Quantification of palaeo pH and palaeo CO2 from marine proxies requires the use of apparent equilibrium constants (K∗’s). The K∗’s required to calculate seawater carbonate chemistry are described by empirically determined calibrations, and for palaeoseawater these calibrations must be adjusted to account for changes in seawater composition. There are a number of possible calibrations that can be used to calculate K∗’s, and each software package for calculating carbonate chemistry separately implements these K∗ calibrations, which are manually verified against previous implementations. Palaeo applications typically only implement a single calibration for each K∗, but have additional complexity from the need to adjust each calibration for changing seawater composition through time. The fragmented approach to K∗ calculation can result in unintended and difficult to resolve discrepancies between outputs calculated by different pieces of software. We present “Kgen,” a synchronised collection of three pieces of software to consistently calculate palaeoseawater K∗’s in Python, R, and Matlab. Kgen provides a simple, and nearly identical interface in each language. Through use of a Continuous Integration/Continuous Delivery (CI/CD) pipeline, Kgen guarantees consistent outputs between languages by automatically cross‐checking results from all three implementations. Unifying the approach to K∗ calculation in this way provides an extensible platform for verifiable K∗ generation for palaeoseawater, which can be integrated into existing carbon speciation calculators to improve the consistency of results.